Polymer-Based Drug-Free Therapeutics for Anticancer, Anti-Inflammatory, and Antibacterial Treatment - Tavares, Marina Rodrigues; Pechar, Michal; Chytil, Petr; Etrych, Tomáš (Macromolecular bioscience, 2021)
This paper summarizes the area of biomedicinal polymers, which serve as nanomedicines even though they do not contain any anticancer or antiinflammatory drugs. These polymer nanomedicines with unique design are in the literature highlighted as a novel class of therapeutics called "drug-free macromolecular therapeutics." Their therapeutic efficacy is based on the tailored multiple presentations of biologically active vectors, i.e., peptides, oligopeptides, or oligosaccharides. Thus, they enable, for example, to directly induce the apoptosis of malignant cells by the crosslinking of surface slowly internalizing receptors, or to deplete the efficacy of tumor-associated proteins. The precise biorecognition of natural binding motifs by multiple vectors on the polymer construct remains the crucial part in the designing of these drug-free nanomedicines. Here, the rationales, designs, synthetic approaches, and therapeutic potential of drug-free macromolecular therapeutics consisting of various active vectors are described in detail. Recent developments and achievements for namely B-cell lymphoma treatment, Gal-3-positive tumors, inflammative liver injury, and bacterial treatment are reviewed and highlighted. Finally, a possible future prospect within this highly exciting new field of nanomedicine research is presented.
Keywords: nanomedicína; Anti-Bacterial Agents; Anti-Inflammatory Agents; Macromolecular Substances; Neoplasms; antiflogistika; nádory; Antineoplastic Agents; makromolekulární látky; lékové transportní systémy; antibakteriální látky; Nanomedicine; Polymers; Drug Delivery Systems; protinádorové látky; Humans; lidé; polymery